2D hydrodynamic simulations of a variable length gas target for density down-ramp injection of electrons into a laser wakefield accelerator - Kononenko,O; Lopes,NC; Cole,JM; Kamperidis,C; Mangles,SPD; Najmudin,Z; Osterhoff,J; Poder,K; Rusby,D; Symes,DR; Warwick,J; Wood,JC; et al. (Nuclear Instruments & Methods in Physics Research Section A - Accelerators Spectrometers Detectors and Associated Equipment, 2016)
In this work, two-dimensional (2D) hydrodynamic simulations of a variable length gas cell were performed using the open source fluid code OpenFOAM. The gas cell was designed to study controlled injection of electrons into a laser-driven wakefield at the Astra Gemini laser facility. The target consists of two compartments: an accelerator and an injector section connected via an aperture. A sharp transition between the peak and plateau density regions in the injector and accelerator compartments, respectively, was observed in simulations with various inlet pressures. The fluid simulations indicate that the length of the down-ramp connecting the sections depends on the aperture diameter, as does the density drop outside the entrance and the exit cones. Further studies showed, that increasing the inlet pressure leads to turbulence and strong fluctuations in density along the axial profile during target filling, and consequently, is expected to negatively impact the accelerator stability.